Antioxidant and Antibacterial Activities of Silver Nanoparticles Biosynthesized by Leaf Foeniculum vulgare Mill. Ethanolic Extract - Nindita Clourisa Amaris Susanto; Dian Eka Ermawati; Sholicha Rohmani; Fitria Lidini Hanifah; Fadhila Dian Nafisa; Echa Hana Prastia; Siti Nurkhasanah; Anis Laela Megasari; Aptika Oktaviana Trisna Dewi (Jurnal Penelitian Pendidikan IPA, 2025)
Silver nanoparticles can be synthesized using biosynthesis methods assisted by plant extracts and can be applied as antibacterials. Hence, this study aimed to synthesize silver nanoparticles from different concentrations of AgNO3 precursor solutions using ethanol extract from fennel leaves. The influences of various AgNO3 concentrations and the volume ratios of AgNO3 solutions and leaf extracts on the activities were observed. The samples were investigated using a UV-Vis spectrophotometer, and the Surface Plasmon Resonance (SPR) absorbance was attained at 410-415 nm, representing the silver nanoparticle formation. The findings showed that the optimal ratio of precursor solution and extract was 10:1. In contrast, the optimal temperature was at 70 ° C. The size of nanoparticles was estimated using the Particle Size Analyzer (PSA), exhibiting that the different AgNO3 concentrations did not significantly change their sizes. The yields demonstrated that the antioxidant activities for nanoparticles synthesized with AgNO3 concentrations of 0.001 and 0.005 M were 153.56 ± 0.09 μg/mL and 0.005 M 111.42 ± 0.15μg/mL, respectively. The results showed higher inhibition zones of antibacterial activity obtained by silver nanoparticles with 0.005 M AgNO3 as compared to those of 0.001 M AgNO3.